Video Emergency Calls in Medical Dispatching: A Scoping Review - Sýkora, Roman; Peřan, David; Renza, Metoděj; Bradna, Jan; Smetana, Jiří; Duška, František (Prehospital and disaster medicine, 2022)
BACKGROUND: Video emergency calls (VCs) represent a feasible future trend in medical dispatching. Acceptance among callers and dispatchers seems to be good. Indications, potential problems, limitations, and directions of research of adding a live video from smartphones to an emergency call have not been reviewed outside the context of out-of-hospital cardiac arrest (OHCA). OBJECTIVE: The main objective of this study is to examine the scope and nature of research publications on the topic of VC. The secondary goal is to identify research gaps and discuss the potential directions of research efforts of VC. DESIGN: Following PRISMA-ScR guidelines, online bibliographic databases PubMed, Web of Science, SCOPUS, Google Scholar, ClinicalTrials.gov, and gray literature were searched from the period of January 1, 2012 through March 1, 2022 in English. Only studies focusing on video transfer via mobile phone to emergency medical dispatch centers (EMDCs) were included. RESULTS: Twelve articles were included in the qualitative synthesis and six main themes were identified: (1) cardiopulmonary resuscitation (CPR) guided by VC; (2) indications of VCs; (3) dispatchers' feedback and perception; (4) technical aspects of VCs; (5) callers' acceptance; and (6) confidentiality and legal issues. CONCLUSION: Video emergency calls are feasible and seem to be a well-accepted auxiliary method among dispatchers and callers. Some promising clinical results exist, especially for video-assisted CPR. On the other hand, there are still enormous knowledge gaps in the vast majority of implementation aspects of VC into practice.
Keywords: výzkumný projekt; Research Design; Emergency Medical Service Communication Systems; Emergency Medical Services; lidé; linka integrovaného záchranného systému; Out-of-Hospital Cardiac Arrest; komunikační systémy urgentních lékařských služeb; Cardiopulmonary Resuscitation; prehospital emergency care; Humans; Emergency Medical Dispatch; urgentní zdravotnické služby; kardiopulmonální resuscitace; dispatching; zástava srdce mimo nemocnici; video emergency call